Left maxillary sinus tumour‐induced hypophosphataemic osteomalacia and combined with thyroid papillary carcinoma: a case report and literature review. Issue 6 (14th June 2020) - Li, Baoxin; Dong, Yuehua; Liu, Dandan; Yao, Qi; Guo, Shuqin; Xin, Huanhuan; Wang, He; Liu, Lifang; Zhang, Yunliang
Abstract: Tumour‐induced osteomalacia (TIO) is a rare disease characterised by hypophosphataemia and clinical symptoms of osteomalacia. Herein we report the case of a 29‐year‐old man who was admitted to hospital with progressive bone pain and was diagnosed with TIO caused by maxillary sinus tumours. In the preoperative evaluation, it was found that the patient had thyroid malignant tumours at the same time. Two operations were performed separately on the left maxillary sinus tumour and thyroid tumour after complete examination. After tumour resections, the symptoms of bone pain were relieved and the level of blood phosphorus was restored, long‐term replacement therapy was needed for thyroid. When a patient is diagnosed with TIO, it is necessary to screen for the presence of other malignant tumours and explore the treatment options in order to benefit patients preferably.